RP-HPLC Estimation of Imipramine Hydrochloride and Diazepam in Tablets - Srikantha, D. (Medknow Publications & Media Pvt Ltd, 2015)
A simple and rapid reversed phase-high performance liquid chromatographic method was developed for simultaneous determination of imipramine hydrochloride and diazepam in pharmaceutical formulations. The elution was done in isocratic mode utilizing a mobile phase consisting of methanol:water:0.1M sodium acetate (30:50:20 v/v/v) on Chromosil C18 column with a flow rate of 1.0 ml/min and with detection at 243 nm. The measured retention time was 3.33±0.02 min for imipramine hydrochloride and 4.64±0.02 min for diazepam. Linearity was measured in the range 25-150 μg/ml for imipramine hydrochloride (r2=0.999) and in the range 5-30 μg/ml for diazepam (r2=0.9994), respectively. The limits of detection and quantitation were 0.03 and 0.1 μg/ml for imipramine hydrochloride and 0.02 and 0.07 μg/ml for diazepam. Satisfactory validation was also obtained from recovery (100.95-101.52% for imipramine hydrochloride and 99.47-100.33% for diazepam) studies, intraday and interday precision (<2%) and robustness results. The reported method was the first study of these drugs in combination and could be employed for routine quantitative determination of imipramine hydrochloride and diazepam in tablets.